Exercises as a Tool for Developing Student Agency in Language Education - Ilchenko , Valeriia; Startseva , Natalya; Карпенко, Олена (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article examines student agency as a set of motivational, cognitive, emotional, and volitional characteristics of the student, which ensures their ability to initiate, control, and direct their own learning – of a foreign language in particular – and reflect on its effectiveness. The theoretical foundations of student agency and the four main approaches to its definition – socio-cultural, psychological, sociological and socio-cognitive – are outlined. The existing typology of student agency encompassing self-directed, collaborative, technological, culture-oriented, research, reflexive, and action-oriented student agency, is analysed and its manifestations are specified with regard to the disciplinary dimension. It is emphasized that student agency is not a permanent feature; it is formed and activated in the process of student interaction with the educational environment conditioned by educational norms and regulations, teacher’s expectations, and traditions of an educational establishment. A significant role in this process is played by teaching methods, types of exercises and the degree of autonomy provided to the student in the learning process. The relationship between the types of student agency and learning exercises that can form its individual types is established. It is determined that different types of exercises feature different agency-forming potential. It is noted that the key means of forming student agency is productive exercises, since they integrate the cognitive, social, reflexive, and functional components of student learning activity. Reproductive and productive-reproductive exercises acquire agency-forming potential, provided that such exercises are used in the educational process focused on the subject activity, their reflection and conscious acquisition of language as a tool for everyday and professional interaction. The authors emphasize the need for an optimal balance between the use of different types of exercises to ensure the formation of sustainable and comprehensive agency in the subject of the educational process, since this approach will maximize the effectiveness of the educational process as a whole.